Applied mechanics and materials I : selected, peer reviewed papers from the 2012 International Conference on Applied Mechanics and Materials (ICAMM 2012), November 24-25, 2012, Sanya, China - International Conference on Applied Mechanics and Materials (ICAMM 2012) (2012 : Sanya, China); Li, Guangfan, editor; Chen, Chaoche, editor (Durnten-Zurich : Trans Tech Pub., 2013)
Includes bibliographical references and index